Strategi Warung Kopi dalam Meningkatkan Minat Pelanggan: Perspektif Fiqh Muamalah - Agus Syaputra; Syawaluddin Syawaluddin (Al-Widad, 2022)
This study is motivated by the rapid growth of coffee shop businesses in Langsa City, which has led to increasingly intense business competition, prompting business owners to implement various marketing strategies to attract customers. However, in practice, there are still marketing strategies that potentially create unfair business competition, such as setting prices below market value and promotional concepts that are not fully aligned with the principles of fiqh muamalah. This study aims to analyze coffee shop marketing strategies in increasing customer interest and to examine their conformity with the perspective of fiqh muamalah. This research employed a field research method using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving coffee shop owners and customers in Langsa City. The results show that the marketing strategies implemented include friendly service, supporting facilities, menu variations, strategic locations, and promotions in the form of bonuses and free drinks. From the perspective of fiqh muamalah, marketing strategies are permissible as long as they do not harm others, uphold honesty, and do not create unfair business competition.